Reversible Deafness and Blindness in a Patient with Cryptococcal Meningitis in Tanzania - Douglas-Vail, Matt (Infect Dis Rep, 2015)
Cryptococcal meningitis is a common and devastating complication of advanced HIV, and is most prevalent in low resource settings in sub Saharan Africa. Raised intracranial pressure is one of the hallmarks of the disease, which can lead to visual and hearing loss and ultimately death. We present the case of a patient with visual and hearing impairment secondary to Cryptococcal meningitis successfully managed by serial cerebrospinal fluid drainage. This case highlights some of the challenges of managing this severe opportunistic infection in a low resource setting.